Calanus spp. in the Arctic ecosystem - a story on predation, distribution and methodology - Vogedes, Daniel Ludwig (UiT The Arctic University of Norway, 2014)
Papers number 5 and 6 of the thesis are not available in Munin due to publishers' restrictions: 5. Daase, M., Eiane, K., Aksnes, D. L. and Vogedes, D.: 'Vertical distribution of Calanus spp. and Metridia longa at four Arctic locations', Marine Biology Research, 4(2008), 193-207, available at http://dx.doi.org/10.1080/17451000801907948 6. Berge, J., Cottier, F., Last, K. S., Varpe, Ø., Leu, E., Søreide, J., Eiane, K., Falk-Petersen, S., Willis, K., Nygard, H., Vogedes, D., Griffiths, C., Johnsen, G., Lorentzen, D. and Brierley, A. S.: 'Diel vertical migration of Arctic zooplankton during the polar night', Biology Letters, 5(2009), 69-72, available at http://dx.doi.org/10.1098/rsbl.2008.0484 The calanoid copepods of the genus Calanus (C. finmarchicus, C. glacialis and C. hyperboreus) are key elements in the Arctic ecosystem. They link primary producers (ice algae, phytoplankton) and higher trophic levels through their ability to convert low energy carbohydrates and proteins to high energy wax esters. This energy is stored in a separate and conspicuous lipid sac. This ability to store large amounts of compact energy is considered an essential adaptation towards the strong seasonality in the Arctic environments. Also the calanoid copepods are known to conduct pronounced seasonal vertical migration and diapause at depth. Due to the large amount of stored energy, Calanus spp. is a preferred prey for a number of planktivorous predators such as herring, polar cod and little auks. The three Calanus spp. share a very similar morphology but have a very different life history and they are bound to different types of water masses: C. finmarchicus has a one year life cycle, indicator of Atlantic water; C. glacialis 1-3 year cycle, indicator of Arctic shelf water; C. hyperboreus 1-5 years, indicator of Arctic water. For this reason the Calanus spp. have long been considered a reliable climate indicator species. Also, they vary in size and thus in total amount of stored lipids, an important factor for those species foraging ...